FTA in a Nutshell. Cracking issues, spreading solutions - Gitz, V.; Meybeck, A.; Coccia, Federica; Ricci, F.; Kiczkajlo, M.; Brady, M.A.; Boot, R.; Elias, M.; Jamnadass, Ramni; Kettle, Christopher J.; Li, Y.; Martius, M.; et al. (CGIAR Research Program on Forests, Trees and Agroforestry, 2022)
The CGIAR Research Program on Forests, Trees and Agroforestry (FTA), created in 2011, is the world’s largest research for development program focused on the role of forests, trees and agroforestry for sustainable development, food security and climate action. At the heart of the program is the vision that forests, trees and agroforestry, when adequately used, managed and governed, in an evidence-based and inclusive way, can play a central role in sustainable development by improving production systems, ensuring food security and nutrition, enhancing people’s livelihoods and addressing climate change.